THE PECULIARITIES OF NEWSPAPER STYLE IN ENGLISH - Shakhnoza Tokhirova (Web of Journals Publishing, 2025)
Newspaper style in English is marked by a set of distinctive features that cater to the demands of mass media communication. These features include a clear structure, objective tone, concise language, and the prioritization of essential information. This paper explores the key characteristics of newspaper style, examining how they facilitate effective communication of news. By analyzing aspects such as syntax, layout, vocabulary, and tone, the article highlights the ways in which journalistic writing differs from other forms of prose.
Keywords: Newspaper style, inverted pyramid, conciseness, objectivity, active voice, headlines, lead paragraph, journalistic writing, news reporting, language, tone, layout, quotations, brevity, clarity, neutrality, media communication, journalistic conventions, print journalism, writing style.